Acute hepatitis in a paediatric patient: immune-mediated drug-induced liver injury or albendazole-induced autoimmune hepatitis? - Nataša Dragutinović; Aleksandra Barać; Goran Stevanović; Irena Đorđić; Bianca Paglietti; Jelena Micić; Ema Aleksić; Jelena Stojnić; Jelena Martinov Nestorov (Journal of Infection in Developing Countries)
Introduction: Drug-induced liver injury (DILI) is one of the most common causes of liver damage. A large number of drugs, dietary supplements, and herbal medications can cause hepatotoxicity. In some situations, it is difficult to distinguish between DILI and autoimmune hepatitis, especially when the mechanism is immune-mediated. Albendazole is a drug that has been used for decades for the treatment of parasitic infections in humans. One of the side effects is liver enzyme elevation, but rarely requires the discontinuation of therapy. Previous experience has shown that hypersensitivity is the most common mechanism of albendazole hepatotoxicity.